Augustine’s critique of representation in arts: Confessions - Tamošaitis, Mantas (Literatūra, 2019)
This article is concerned with the critique of representation in art found in Augustine’s Confessions. The aim of the author is not only to reveal the fundamental influence of Plato and Aristotle on Augustine’s criticism, but to show the unique aspects of Augustine’s thought. The article considers Augustine’s critique of art in the Confessions to be three-fold: the ontological critique, the ethical (psychological) critique of intention and the critique of pagan ethos in art. The article considers the ontological critique as based on the neoplatonic dualism of body and soul as well as the platonic concept of image. Therefore Augustine considers artistic representation to be three-times removed from reality and sees the experience of God as the perfect aesthetical experience. Author states that the ethical critique considers art as a form of idolatry, which projects the innermost desires of the soul (the desire of God) onto the material pleasures of the outer world. Even though Augustine’s thinking is based on the Aristotelian concept of catharsis, the conclusions are entirely different – in Augustine’s opinion the aesthetical experience does not free the audience of its corporal appetites. Quite the contrary, the appetites get more intense. It should also be brought to the attention of the reader, that Augustine holds a certain hostility towards theatre and pagan literature as a pagan social practices. Augustine develops the thought of these Greek philosophers from the Christian point of view and bases his ethical critique of the aesthetic experience along with the critique of aesthetic practices on it. Moreover, he is more open to the concept of art as a fiction than Plato.